Implementasi Moderasi Beragama Dalam Pembangunan Ekonomi Dan Pemberdayaan Masyarakat - Tursity Attatwa Idinastika (Yayasan Salam Cerdas Al-Fattah, 2025)
This research discusses the strategic role of religious moderation in supporting populist economic development and village community empowerment. Religious moderation that prioritizes the values of balance, tolerance, and justice contributes to creating social cohesion, which is an important foundation for inclusive and sustainable village development. Through a qualitative approach with a literature study method, this research examines scientific literature and policy documents to understand the relationship between moderate religious values and village socio-economic dynamics. The results show that the implementation of religious moderation encourages collective participation, strengthens social capital, and facilitates cross-group cooperation in economic activities such as cooperatives, MSMEs, and BUMDes. Case studies in various villages show that religious forums, gotong royong activities, and tolerance value education can increase solidarity and local economic productivity. Thus, religious moderation is not only relevant as a theological concept, but also as a practical approach to strengthen the capacity of village communities. This research recommends mainstreaming religious moderation in village development policies through collaboration between the government, religious leaders, and civil society to realize peaceful, prosperous, and independent villages.